1. y = x^68 * cosx
y ' = (x^68)' cosx + (cosx)' x^68 =
= 68* x^67* cosx - x^68 * sinx =
= x^67* (68 cosx - x sinx)
2. y = x^53 * sinx
y ' = (x^53)' * sinx + x^53 * (sinx)' = 53*x^52*sinx+x^53*cosx =
x^52*(53sinx+cosx)
3. Аналогично, попробуй сам, если не получится, то отпишись
Пошаговое объяснение:
Пью пивасик, сорян
1. y = x^68 * cosx
y ' = (x^68)' cosx + (cosx)' x^68 =
= 68* x^67* cosx - x^68 * sinx =
= x^67* (68 cosx - x sinx)
2. y = x^53 * sinx
y ' = (x^53)' * sinx + x^53 * (sinx)' = 53*x^52*sinx+x^53*cosx =
x^52*(53sinx+cosx)
3. Аналогично, попробуй сам, если не получится, то отпишись
Пошаговое объяснение:
Пью пивасик, сорян